Emergence of rationally designed therapeutic strategies for breast cancer targeting DNA repair mechanisms - Rowe, Bryan P (BioMed Central, 2010)
Accumulating evidence suggests that many cancers, including BRCA1- and BRCA2-associated breast cancers, are deficient in DNA repair processes. Both hereditary and sporadic breast cancers have been found to have significant downregulation of repair factors. This has provided opportunities to exploit DNA repair deficiencies, whether acquired or inherited. Here, we review efforts to exploit DNA repair deficiencies in tumors, with a focus on breast cancer. A variety of agents, including PARP (poly [ADP-ribose] polymerase) inhibitors, are currently under investigation in clinical trials and available results will be reviewed.